Remote Forcing of Shelf Flows by Density Gradients and the Origin of the Annual Mean Flow on the Mid‐Atlantic Bight. Issue 7 (2nd July 2018) - Pringle, James M.
Abstract: In the annual mean, a southwestward along‐isobath flow exists in the Mid‐Atlantic Bight. It has been shown to be driven neither by local winds, which are too weak and in the wrong direction to explain the flow, nor by local density gradients, which are too weak to explain the flow. Prior work has established that the mean flow is part of a local alongshore momentum balance between bottom friction and along‐isobath pressure gradient; but that work does not explain the origin of the pressure gradient. A simple model of shelf flows driven by density anomalies elsewhere on the shelf is developed. This model is used to argue that the annual average flow is consistent with remote forcing by density gradients on the shelf along the southern edge of the Laurentian Channel and the Scotian Shelf. These density gradients are largely caused by freshwater input from the Saint Lawrence River, and their effect when integrated over the Laurentian Channel, Scotian Shelf, and Gulf of Maine shows only a weak seasonal signal. Key Points: Density anomalies on a shelf drive flows on the shelf downwave of the anomaly—a low‐density anomaly drives a flow in the downwave direction The mean flow in the Mid‐Atlantic Bight is largely driven by density gradients in the Gulf of Maine and Laurentian Channel Density anomalies on a shelf can drive cross‐shelf transport outside of the density anomaly